Innate lymphoid cells in allergic and nonallergic inflammation - Morita, Hideaki; Moro, Kazuyo; Koyasu, Shigeo (Journal of allergy and clinical immunology, 2016)
In the last decade, the full picture of the role of innate lymphoid cells (ILCs) has been gradually revealed. ILCs are classified into 3 groups based on their transcription factors and cytokine production patterns, which mirror helper T-cell subsets. Unlike T cells and B cells, ILCs do not have antigen receptors. They promptly respond to multiple tissue-derived factors, such as cytokines and alarmins, and produce multiple proinflammatory and immunoregulatory cytokines. It has been reported that ILC-derived cytokines are important for the induction and regulation of inflammation. Accumulating evidence suggests that ILCs play substantial roles in protection against infection and the pathogenesis of inflammatory diseases, such as allergic diseases and autoimmune diseases. Different ILC subsets localize in distinct tissue/organ niches and receive tissue-derived signals on different types of inflammation, which allows them to acquire diverse phenotypes with specialized effector capacities. In this review we highlight the roles of ILCs in a variety of organs, such as the airway, skin, and gastrointestinal tract, in the context of allergic and nonallergic inflammation.